Caracterização de um produto odontológico à base de própolis: ações antibacteriana e imunomoduladora - Santiago, Karina Basso [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The caries and periodontal disease are infectious diseases, reflecting failure to balance the oral microbiota, whose agents can be transmitted. Chlorhexidine has been used as anti-caries agent, but its use is controversial due to the occurrence of side-effects. Thus, there is a need to search for new products with antimicrobial activity and fewer side-effects. Propolis is a resinous product produced by bees from different parts of the plants, and stands out for its biological and pharmacological properties, and the application possibility in the pharmaceutical and food industry. In this project, we aimed to investigate propolis, an antimicrobial agent (chlorhexidine) and the combination propolis/chlorhexidine, directly on S. mutans and the action of human monocytes against this bacteria. The quality of propolis-based odontological product was analysed with regard to its stability and possible contamination for 120 days. We evaluated the effect of this product on S. mutans determining the minimum inhibitory concentration and minimum bactericidal concentration, and its effect on human monocytes, evaluating cell receptors expression, the NF-kB signaling pathway, the production of pro- and anti-inflammatory cytokines, and the bactericidal activity of these cells against S. mutans. Together, data showed that propolis/chlorhexidine in combination was palatable and contaminant-free, besides inhibiting the growth of S. mutans. The product may favor the recognition of antigens by human monocytes, activate the NF-kB signaling pathway and increase the bactericidal activity of monocytes against S. mutans. Also, the combination played an anti-inflammatory role in cytokine production, what can be beneficial in the treatment of periodontal diseases. The findings open perspectives for further research, denoting the practical application of this research and its implications for the pharmaceutical industry

A cárie e a doença periodontal são doenças infecciosas que refletem falha no equilíbrio da microbiota bucal, e seus agentes podem ser transmissíveis. A clorexidina tem sido utilizada como agente antimicrobiano no combate à carie, porém seu uso é controverso devido à ocorrência de efeitos colaterais. Assim, tem sido incansável a busca de novos produtos com atividade antimicrobiana e com menor efeito colateral. A própolis é um produto resinoso, elaborado pelas abelhas a partir de diversas partes das plantas, e se destaca por suas propriedades biológicas e farmacológicas, e pela possibilidade de aplicação na indústria farmacêutica e alimentícia. Neste projeto, visamos comparar a própolis com um agente antimicrobiano (clorexidina), bem como a combinação própolis/clorexidina, diretamente sobre Streptococcus mutans ou sobre a ação de monócitos humanos contra esta bactéria. Para tal, monitoramos a qualidade do produto odontológico elaborado à base de própolis em relação à sua estabilidade e possível contaminação durante 120 dias. Avaliamos o efeito do produto sobre S. mutans, determinando a concentração inibitória mínima e a concentração bactericida mínima, bem como seu efeito sobre monócitos humanos, avaliando a expressão de receptores celulares, a via de sinalização do NF-kB, a produção de citocinas pró- e antiinflamatórias, e a atividade bactericida de monócitos contra este agente causador da cárie. Tomados em conjunto, os dados evidenciaram que o produto apresentou-se palatável e livre de contaminantes, além de inibir o crescimento de S. mutans. Este produto pode favorecer o reconhecimento de antígenos por monócitos, ativar a via de sinalização do NF-kB e aumentar a atividade bactericida de monócitos humanos contra S. mutans. Ademais, o produto também desempenhou papel anti-inflamatório quanto à produção de citocinas, o que pode trazer benefícios no tratamento de doenças...
Keywords: Própole; Antibacterianos; Streptococcus mutans; Monocitos; Placa dentária; Citocinas; Clorexidina; Chlorhexidine